Optimizing Health Research Budget Allocation through Reformulation of State Budget Funding Regulations - Ferianasari, Ineke Winda; Amelia, Tina (International Journal of Social Service and Research, 2025)
Health research is crucial for enhancing medical services and improving community welfare in Indonesia. However, challenges such as uneven allocation, limited transparency, and insufficient integration of research findings into health policy continue to hinder the effectiveness of research funding. This study aims to evaluate the policies and decision-making processes involved in the procurement of health research budgets in Indonesia and propose legal formulations to ensure that these funds are managed in a fair, transparent, and accountable manner. The study utilizes an empirical juridical research method with legislative, conceptual, and comparative approaches. Data were gathered through interviews, observations, and literature studies, followed by descriptive-analytical analysis using case studies and legal theories on utility, legislation, and legal reform. The findings reveal that the allocation of health research budgets has not fully adhered to principles of equity, and research outcomes are often not incorporated into policy. Budget allocations are still influenced by political interests, and cross-agency coordination remains weak. Legal reforms are necessary to make the budget management process more participatory, measurable, and evidence-based. Transparent and adaptive legal reforms are crucial to optimizing state budget use in health research. Additionally, establishing a digitized surveillance system, multi-stakeholder forums, and enhancing the capacity of research and bureaucratic sectors are essential to fostering an inclusive and sustainable medical innovation ecosystem.